Video-mediated listening and multiliteracies - Losada Rivas, Jhon Jairo; Suaza Cardozo, David Alfonso (Colombian Applied Linguistics Journal, 2018)
Based on the need to explore the incidence of multiliteracies in EFL education, this study presents the ways in which video-mediated listening activities contribute to the construction of new meanings in an EFL setting. This qualitative action research was carried out at a private school from Huila, Colombia with 11th grade students who had difficulties with their foreign language listening skills. Pedagogical interventions involved all students from the course (16 pupils); nonetheless, convenience sampling was used to narrow research data to six participants. Our research objective was to analyze how the construction of meaning was developed through the implementation of video-mediated listening activities under a multiliteracies approach. Findings show that students established interactions with different sources of information provided by the videos that enabled them to create and disclose new meanings derived from their transformed interpretations. The results also shed light on how video-mediated listening activities foster students’ understandings of their own learning processes.